NIR-II imaging of hepatocellular carcinoma based on a humanized anti-GPC3 antibody. Issue 1 (29th November 2021) - Shi, Hui; Huttad, Lakshmi Vageesh; Tan, Mingdian; Liu, Hongguang; Chua, Mei-Sze; Cheng, Zhen; So, Samuel
Abstract : A NIR-II fluorescence probe was synthesized based on a humanized anti-GPC3 antibody and ICG for HCC targeted NIR-II imaging. GPC3-ICG showed specific HCC cell line and Huh-7 tumor targeting imaging capability. Abstract : Liver cancer, of which hepatocellular carcinoma (HCC) is the most common form, is one of the most lethal cancers worldwide. The five-year survival rate for HCC is below 9%, which can be attributed to late diagnosis and limited treatment options at the late stage. Therefore, safe and efficient imaging strategies are urgently needed to facilitate HCC diagnosis and stage evaluation. The development of the second near infrared window (NIR-II, 1000–1700 nm) fluorescence imaging offers the advantages of enhanced resolutions, deeper penetration depth, and less autofluorescence compared to traditional NIR-I window (700–900 nm) imaging. Herein, an HCC targeted NIR-II fluorescent probe, GPC-ICG, was developed by labelling a humanized anti-GPC3 monoclonal antibody with indocyanine green (ICG). Compared to the negative control IgG-ICG probe, the GPC3-ICG probe demonstrated specific GPC3 targeting capability in vitro . And for GPC3 positive Huh-7 tumor bearing mice, the GPC3-ICG probe specifically accumulated in subcutaneous xenografts, with a tumor–background ratio (TBR) of up to 3. The NIR-II imaging of mice organs ex vivo also indicated that GPC3-ICG specifically targeted Huh-7 tumor tissue. Overall, GPC3-ICG is a promising NIR-II probe for GPC3 targeted imaging of HCC.